Carrier envelope phase sensitivity of photoelectron circular dichroism - Hanus, Vaclav; Kangaparambil, Sarayoo; Richter, Martin; Hassfurth, Lukas; Dorner-Kirchner, Martin; Paulus, Gerhard G.; Xie, Xinhua; Baltuska, Andrius; Gräfe, Stefanie; Zeiler, Markus (Physical Chemistry Chemical Physics, 2023)
We report on a combined experimental and numerical study of photoelectron circular dichroism (PECD) induced by intense few-cycle laser pulses, using methyloxirane as the molecular example. Our experiments reveal a remarkably pronounced sensitivity of the PECD strength of double-ionization on the carrier-envelope phase (CEP) of the laser pulses. By comparison to the simulations, which reproduce the measured CEP-dependence for specific orientations of the molecules in the lab frame, we attribute the origin of the observed CEP-dependence of PECD to the CEP-induced modulation of ionization from different areas of the wave functions of three dominant orbitals.
CRIS-Team Scopus Importer:2023-04-20